2019
DOI: 10.3390/geosciences9030142
|View full text |Cite
|
Sign up to set email alerts
|

Seafloor Classification in a Sand Wave Environment on the Dutch Continental Shelf Using Multibeam Echosounder Backscatter Data

Abstract: High resolution maps of sandy seafloors are valuable to understand seafloor dynamics, plan engineering projects, and create detailed benthic habitat maps. This paper presents multibeam echosounder backscatter classification results of the Brown Bank area of the North Sea. We apply the Bayesian classification method in a megaripple and sand wave area with significant slopes. Prior to the classification, corrections are implemented to account for the slopes. This includes corrections on the backscatter value and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 25 publications
0
38
0
Order By: Relevance
“…The few field studies available on sand waves have mostly observed coarser sediments on crests compared to troughs, but did not consistently study the composition of slopes. Also, the focus has been on grain size rather than on related components such as biogeochemical compounds [3,5,21,34,[44][45][46][47][48][49]. [23,26,[30][31][32][33] and sand wave emergence and growth.…”
Section: Introductionmentioning
confidence: 99%
“…The few field studies available on sand waves have mostly observed coarser sediments on crests compared to troughs, but did not consistently study the composition of slopes. Also, the focus has been on grain size rather than on related components such as biogeochemical compounds [3,5,21,34,[44][45][46][47][48][49]. [23,26,[30][31][32][33] and sand wave emergence and growth.…”
Section: Introductionmentioning
confidence: 99%
“…Smaller scaled megaripples are found superimposed on the sand waves. These megaripples have wavelengths of ∼10 m, amplitudes of ∼0.5 m, and an east-west orientation (Koop et al, 2019). Both sand waves and megaripples are known to migrate.…”
Section: Study Areamentioning
confidence: 99%
“…In 2017, S. spinulosa reefs were discovered for the first time on the Dutch Continental Shelf, in the Brown Bank area (van der . This area is characterized by large-scale (5-10 km) tidal ridges, superimposed with dynamic, migrating bedforms at smaller scales: sand waves with wavelengths of ∼200 m, and megaripples with wavelengths of ∼10 m (Knaapen, 2009;van Dijk et al, 2012;Koop et al, 2019). In addition, the area is fished at least once a year by demersal fisheries (van der .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the horizontal displacement of the sand wave, the ner grains originating from earlier deposits become mixed in the top layer, leading to a ning of the stoss slope. In contrast to the lack of eld evidence for sand waves, a study by Koop et al (2019) into migrating mega ripples did reveal a similar sorting pa ern where both the lee and stoss side are ner than the crest and trough. However, all these eld data were obtained by box-and multicorers which only describe the upper part (∼ 20 cm) of the bed, so that the internal structure cannot be assessed.…”
Section: F Smentioning
confidence: 80%
“…e bed of the North Sea contains a great variety of sandy sediments, which show large spatial variations (Damen et al, 2018a). However, within areas with marine bed forms sediments tend to be remarkably well sorted, both on a small scale (mega ripples (Koop et al, 2019)) and on a large scale (sand banks (Verfaillie et al, 2006;Van Dijk et al, 2012)).…”
mentioning
confidence: 99%